PLK1 expression and BI 2536 effects in childhood acute lymphoblastic leukemia. Issue 7 (12th February 2014) - Oliveira, J.C.; Pezuk, J.A.; Brassesco, M.S.; Morales, A.G.; Queiroz, R.G.P.; Scrideli, C.A.; Tone, L.G.
<x xml:space="preserve">Abstract</x> Background Polo‐like kinase 1 (PLK1) is a conserved kinase that mediates various mitotic events. Compelling data have repeatedly demonstrated its upregulation in different neoplasia, being frequently associated with poor prognosis. However, in childhood acute lymphoblastic leukemia (ALL), no studies have yet been conducted. Procedure PLK1 expression and association with biological features were evaluated in 65 consecutively diagnosed childhood ALL samples by quantitative real‐time PCR. Moreover, the effects of a specific PLK1 inhibitor, BI 2536, was tested against a panel of nine ALL cell lines at nanomolar concentrations (10, 50, 100 nM). Results The mRNA expression of PLK1 showed great variability in pediatric ALL, but no difference was evidenced compared to normal bone marrow. Additionally, no association was found between PLK1 mRNA expression with any clinical or biological features. Alternatively, high mRNA expression of PLK1 was present in ALL cell lines. In vitro treatment with BI 2536 strongly diminished growth, while presenting significant reduction in colony formation capacity and increased apoptosis rates. Moreover, strong G2/M arrest was detected suggesting important impaired proliferation after treatment. Conclusions PLK1 mRNA expression level is not associated with prognosis in childhood ALL; however, considering the great variability observed in the sample and the in vitro experiments presented herein, BI 2536 treatment might serve as a promising therapeutic to enhance the efficacy of conventional treatment modalities in some childhood ALL cases. Pediatr Blood Cancer 2014;61:1227–1231. © 2014 Wiley Periodicals, Inc.